A facile and diverse synthesis of coumarin substituted spirooxindole and dispiro oxindole-pyrrolizidine/pyrrolothiazole/pyrrolidine derivatives via 1, 3-dipolar cycloaddition. (2nd July 2021) - Gong, Panwei; Ma, Ying; Wang, Xingyu; Yu, Lu; Zhu, Songlei
Abstract: A diverse series of coumarin substituted spirooxindole and dispirooxindole-pyrrolizidine/pyrrolothiazole/pyrrolidine derivatives have been obtained via azomethine ylide specific three-component 1, 3-dipolar cycloaddition reaction. This protocol features include operational simplicity, mild reaction conditions, high yields and a broad substrate scope. Graphical abstract: Image 1